2017
DOI: 10.1002/acr.22973
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Earthquake Exposure and Midlife Uric Acid Levels Among Chinese Adults

Abstract: Prenatal exposure to the earthquake was associated with higher serum uric acid and higher odds of hyperuricemia in early adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Table SI 11.3 shows data collected on the relationship between PS and offspring's glucose metabolism. Four studies on offspring's glucose and PS were identified in our review and all of them found no association between glucose and PS (negative life events, job strain and exposure to earthquake) [41,47,54,55]. We found only one study reporting on PS and insulin without significant assoaciations [41].…”
Section: Systematic Review On the Relationship Between Ps And Blood Pmentioning
confidence: 82%
See 3 more Smart Citations
“…Table SI 11.3 shows data collected on the relationship between PS and offspring's glucose metabolism. Four studies on offspring's glucose and PS were identified in our review and all of them found no association between glucose and PS (negative life events, job strain and exposure to earthquake) [41,47,54,55]. We found only one study reporting on PS and insulin without significant assoaciations [41].…”
Section: Systematic Review On the Relationship Between Ps And Blood Pmentioning
confidence: 82%
“…In one study, the systolic pressure was significantly higher in the prenatal earthquake stress group compared to that in the control group, but no significant differences were found for diastolic pressure [55]. In the other study, prenatal exposure to the earthquake was not associated with systolic or diastolic blood pressure [47].…”
Section: Systematic Review On the Relationship Between Ps And Blood Pmentioning
confidence: 87%
See 2 more Smart Citations
“…Such catastrophic natural disaster places tremendous stress on infants and developing fetuses. In our previous studies, we found that those who experienced Tangshan Earthquake in their early years had an increased risk of elevated resting heart rate, fasting plasma glucose, total cholesterol, higher serum uric acid and higher odds of hyperuricemia as adults (Ji et al, 2017; Li et al, 2017; An et al, 2014). We also found adverse neurocognitive consequences of long‐term prenatal earthquake exposure (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 96%